Strategi Kebijakan Pengembangan Desa Pesisir (Studi di Empat Belas Desa Pesisir di Kabupaten Blitar Provinsi Jawa Timur) - Muhammad Lukman Hakim (Program Studi Administrasi Negara Universitas Serang Raya, 2020)
Research on development policy strategies for coastal areas in Blitar District is important and urgent, considering that there has been a disparity in development between the Blitar North and South Blitar Regions. In terms of community welfare, the Blitar Pesisir Selatan region tends to be poorer, education is still minimal, with poor infrastructure. This can be seen from the Village Development Index of Blitar District. This study seeks to identify the typology of the Village in the Coastal District of Blitar to then formulate a policy development policy for the Coastal Village. In addition to using the ABCD Theory, this study uses the results of the analysis of the Village Build Index and the SWOT analysis. The analysis stage in SWOT is to utilize all data and information in quantitative models of strategy formulation. SWOT analysis is carried out first scanning (scanning) which in essence is a data collection and identification as a pre-analysis. The models used in the SWOT analysis in typology analysis and the development of coastal villages in Blitar Regency are IFAS - EFAS (internal - external strategic factor analysis summary). Internal and external strategy factor analysis is the processing of strategic factors in the internal and external environment by giving a weighting and rating to each strategic factor. Strategic factors are the dominant factors of strengths, weaknesses, opportunities and threats that influence the existing conditions and situations and provide benefits if positive actions are taken. Analyze the internal environment (IFAS) to find out various possible strengths and weaknesses. Strategic issues to be monitored must be determined because these problems might affect development in the future. Analyzing the external environment (EFAS) to find out various opportunities and threats. Through the analysis phase as above, this research is expected to formulate an appropriate policy strategy in developing rural villages in the southern coastal region of Blitar Regency.